Stres Akademik Mahasiswa Dalam Perkuliahan Daring Selama Masa Pandemi Covid-19 - Qatrunada, Arifah; Lathifah, Maghfirotul; Sutijono, Sutijono (Universitas Nusantara PGRI Kediri, 2022)
The phenomenon that occurred in March was Covid-19 Pandemic. It requires all activities at home, including the world of lectures. The lectures are currently conducted online, bringing up many obstacles and complaints felt by students, among them excessive demands for assignments, delayed practice, difficulty in understanding and digesting materials, difficulty with website access, signals that must be stable, related to single tuition payments, and internet quotas, so it can make students become stressed, or what is commonly called academic stress. Academic stress is a pressure experienced by individuals related to academic demands, affecting physical, emotional, behavioral, and cognitive conditions. This study aims to find out the academic stress experienced by students in online lectures. This study represents a qualitative, descriptive type of research approach. The instruments used were questionnaires and interviews. The sample in this study amounted to 98 students. The data analysis techniques are data reduction, presentation, and conclusion withdrawal. The results of this study can be inferred that the 2018 Army Students at X University course online experience academic stress with categories high 37 students, medium 60 students, and low 1 student. Therefore, students are expected to be able to control and adjust to online lectures to minimize academic stress.